﻿A new species of Lumbrineriopsis (Annelida, Eunicida, Lumbrineridae) from southeastern Brazil - Scamparle Teodoro, Nálita Maria; Steiner, Tatiana Menchini; Amaral, Antonia Cecília Zacagnini (ZooKeys, 2023)
Lumbrineriopsis dulcis sp. nov. is morphologically described from the continental shelf and slope of Espírito Santo and the Campos Basin of Rio de Janeiro state, southeastern Brazil, at depths between 14 and 400 m. Lumbrineriopsis mucronata is the only species of the genus recorded until now in Brazil. The new species differs from other congeneric species in its jaw-apparatus morphology with unfused mandibles and a fixed number of simple limbate chaetae and simple, bidentate, hooded hooks in each parapodium. This paper aims to fill the gap in knowledge on the family Lumbrineridae, which has not been studied in Brazil for the last 25 years and provides the first record of the genus from Espírito Santo and Rio de Janeiro states. This record is significant given the damage to the marine ecosystem of the Espírito Santo region due to the 2015 rupture of the Samarco mining company dam, the largest environmental disaster in Brazil’s history. In addition, this region has important environmental conservation units such as Costa das Algas Environmental Protection Area, Santa Cruz Wildlife Refuge, and Comboios Biological Reserve. All these preserved areas are of paramount importance for the protection of marine biological diversity.
World Polychaeta Database (WPolyDb)